Формування стратегії економічної безпеки підприємств дитячого харчування - Скорук, Олена Володимирівна (My University, 2012)
Дисертація присвячена дослідженню теоретичних положень та розробці практичних рекомендацій щодо формування стратегії економічної безпеки підприємств дитячого харчування. In the work the theoretical principles and practical recommendations for the strategy of economic security firms baby food. Carried out evaluation of conceptual approaches to defining the essence of economic security and economic security strategy of the company. The system of negative factors impact on the economic security of the enterprise according to various classification criteria. A modern paradigm of economic security strategy of the enterprise.
Keywords: економічна безпека підприємства; стратегія економічної безпеки; оцінка рівня економічної безпеки; механізм реалізації стратегії; ринок дитячого харчування; economic security of the enterprise; economic security strategy; evaluating the level of economic security mechanism implementation strategy; market for baby food